COST OF ILLNESS ANALYSIS OF EPILEPSY OUTPATIENTS USING VALPROIC ACID, PHENYTOIN AND CARBAMAZEPINE THERAPY IN HOSPITAL IN INDONESIA - Nurmesa, Adi; Putra, Dimas Setyadi; Rachman, Abu; Wahyudi, Wahyudi (Usadha Journal of Pharmacy, 2024)
Epilepsy is a condition of the onset of attacks in the form of abnormal, irregular brain nerve cell movements, occurring repeatedly and causing temporary motor, sensory or mental function disorders. The treatment of epilepsy has costs that must be known, including direct medical costs, indirect medical costs, and indirect costs; this study aims to determine the cost of illness of epilepsy in one hospital in banyuasin regency with retrospective costing in outpatients. The research method used in this study is a cross-sectional study using patient medical record data and cost data taken from BPJS claims data and hospital rate patterns. This study uses the BPJS perspective and societal perspective, the cost data taken from the BPJS perspective is the result of BPJS claims according to the INACBGs. Package tariff and for the socital perspective the data taken is doctor consultation data, administrative costs, laboratory costs, drug costs and transportation costs and lost productivity costs carried out by interview method for 12 months. The results of this study indicate that the cost of epilepsy outpatients from a societal perspective is Rp.3,141,414 and for BPJS perspective is Rp.2,338,567.